Investigation of The Effect of Design Variables on Slip Assembly: Spline Module and Slip Length - Hüseyin Özgürler; Mert Can Kahyalar; Onur Şen (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The driveshaft which transmits the power from the engine to the wheels in the motor vehicles is one of the vital elements in the driveline. Driveshafts have two basic motions depending on the road conditions, angular and axial movements. Angular movement is provided by the universal joints while the axial movement is provided by the slip assembly which involves a group of sliding components. Therefore, the slip assembly is an important part of the drive shaft. Basically, a slip assembly consists of two parts which are connected to each other by means of their spline forms. The parts can move back and forth longitudinally while they transmit the torque thanks to the connection interface of their spline forms. And so, they can slide and adjust the drive shaft lengths due to the position of the axles under road conditions.During the motor vehicle movement, slip assembly are subjected to torsion like the other components on the driveshaft. In this context, spline size and magnitude of the length compensation are highly important in the design process of the slip assembly. In this study, the effect of the spline size and the slip length have been investigated for the yoke shaft design, by using analytical and numerical methods in terms of shear stress. It has been observed that the analytical and the numerical methods give the similar results in shear stress on the pitch diameter of the spline. Thus, the analytical method can be preferred instead of the finite element analysis (FEA), especially considering that the FEA is a time consuming method compared to the analytical method in the design process.